Пейзаж – символ, знак – состояние – украшение - внешнее подобие… - Молчанова-Дудченко, Е.А. (Культура народов Причерноморья, 2013)
Автор в статье делает попытку исторического экскурса становления жанра
изобразительного пейзажа. Показана цепочка метаморфозы пейзажа в условиях цивилизационных
изменений в мире: художественный акт, раскрывающий неисчерпаемую сущность бытия, в Древнем
мире – фон для изображения библейских сюжетов, портретов, мифологических сцен в эпоху
Возрождения – идеализированный образ окружающего мира, эталоны гармоничного пейзажа в XVIIXVIII
веках – деформационный образ, превращающий пейзаж в предлог для отвлеченных построений, в
XX веке.
Ключевые слова: пейзаж, живопись, художественный образ, сюжет, состояние, картина. Автор у статті робить спробу історичного екскурсу становлення жанру образотворчого
пейзажу. Показано ланцюг метаморфоз пейзажу в умовах цивілізаційних змін у світі: художній акт, що
розкриває невичерпну сутність буття, в Стародавньому світі - фон для зображення біблійних сюжетів,
портретів, міфологічних сцен в епоху Відродження - ідеалізований образ навколишнього світу, еталони
гармонійного пейзажу в XVII-XVIII століттях - деформаційний образ, який перетворює пейзаж у привід
для абстрактних побудов, в XX столітті.
Ключові слова: Пейзаж - символ, живопис, художній образ, сюжет, настрій, малюнок. In the article "Landscape – symbol, sign - condition - decoration - external likeness" author is made
attempt to historical excursus of becoming a genre of fine scenery. Chain of metamorphoses of landscape in
circumstances of civilizational change in the world is shown: artistical act, which reveals the inexhaustible
essence of being, in the Antiquity - background for images of biblical scenes, portraits, mythological scenes in
the Renaissance - idealized image of the world, the standards of harmonious landscape in XVII-XVIII centuries -
deformation image, which makes the landscape into a pretext for abstract constructions, in the XX century.
Adducing the examples of landscape-painters from different historical periods, the author reveals the concept of
the landscape as a genre of fine art, in which the main subject of the image is nature, primitive or transformed
by human.
Landscape continues to arouse interest among artists of different directions, in which the brushwork and
technical preferences are unique and original. Among the modern artists have adherents of the old school of
species landscapes, emotional follower’s impressionism, romantic researchers of different states of nature,
formal conceptualist, which compress the reality to geometry and others. They all have their creative views and
everyone tries to share them with the world.
Key words: landscape, painting, artistic image, the story, the state, picture.